Ab initio and semi-empirical computational studies on 5-hydroxy-5,6-di-pyridin-2-yl-4,5-dihidro-2H-[1,2,4]triazine-3-thione - Karakurt, Tuncay; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Elsevier, 2012)
The title compound, 5-hydroxy-5,6-di-pyridin-2-yl-4,5-dihidro-2H-[1,2,4]triazine-3-thione (C13H11 N5OS), was prepared and characterized by electronic spectroscopy and single-crystal X-ray diffraction (XRD). The compound crystallizes in the triclinic space group P-1 with a = 8.5808(8) angstrom, b = 8.7032(7) angstrom, c = 10.0505(9) angstrom, alpha = 84.194( 7)degrees, beta = 75.181(7)degrees and gamma = 63.562(6)degrees. In addition to the molecular geometry, vibrational frequencies and gauge including atomic orbital (GIAO) H-1 and C-13 NMR chemical shift values of the title compound in the ground state have been calculated using the Hartree-Fock (HF) and density functional theory (OFT) methods with 6-31G(d) basis sets. To determine conformational flexibility, the molecular energy profile of the title compound was obtained by semi-empirical (AM1) calculations with respect to the selected torsion angle, which was varied from -180 degrees to + 180 degrees in steps of 10 degrees. The energetic behavior of the title compound in solvent media was examined using the B3LYP method with the 6-31G(d) basis set by applying the Onsager and the Polarizable Continuum Model (PCM). By using TD-DFT method, electronic absorption spectra of the title compound have been predicted and a good agreement with the TO-OFF method and the experimental one is determined. The predicted nonlinear optical properties of the title compound are much greater than ones of urea. In addition, the molecular electrostatic potential (MEP), frontier molecular orbitals (FMO) analysis and thermodynamic properties of the title compound were investigated using theoretical calculations. Published by Elsevier B.V.
Keywords: IR and NMR spectroscopy; Onsager; Ab initio calculations; Electronic structure; NBO analysis